Managing the new workforce international perspectives on the millennial generation - edited by Eddy S. Ng, Sean. (Cheltenham Edward Elgar, 2012)
In a unique historical phenomenon of demographics , a large cohort of post-war Baby Boomers is retiring as a new cadre of younger workers, the twenty-somethings referred to as 'Gen Y' or Millennials, are being recruited to replace them. This workforce of the future comes with their own set of expectations, demands, and work habits. This book provides an understanding of the new workforce in many countries and settings. The international perspective makes it possible to examine cross-cultural similarities and differences in HRM practices.
Includes bibliographical references and index.
Keywords: Personnel management